Recognizing and addressing burnout among healthcare workers in rural Nepal: a proof-of-concept study using Kern’s six-step theoretical framework - Raj Kumar Dangal; Eva Studer; Tula Krishna Gupta; Kristin Nguyen; Amit Suneja; Karuna Khadka; Shailina Bata Shrestha; Bibhav Acharya (BMC Health Services Research)
Abstract Introduction Healthcare provider burnout is highly prevalent and has negative consequences. However, many healthcare workers in LMICs, including Nepal, rarely recognize or ameliorate it. This problem is worse in rural settings. Competency-focused interventions that are developed using theoretical frameworks can address this gap. Methods We used Kern’s framework of curriculum development to create, refine, and assess a theory-driven intervention tailored to the needs and constraints of rural healthcare workers in Nepal. During the first phase, we conducted a targeted needs assessment using an online survey among nine rural primary care physicians working in Charikot Hospital. We then developed learning objectives for knowledge, attitude, and skills domains based on the World Health Organization (WHO) definition of burnout. Then, we created animated educational videos designed to meet the learning objectives. We then implemented the educational intervention with rural physicians and assessed their knowledge, attitudes, and feedback. During the second phase, we further developed the intervention based on findings from the first phase and assessed acceptability, feasibility, and preliminary impact using pre- and post-intervention questionnaires and key informant interviews. Results In the first phase, nine physicians participated in the targeted needs assessment, and eight responded to the post-intervention assessment. In the second phase, 18 attendees completed the pre-intervention burnout assessment, and 16 completed both the pre-test and post-test questionnaires. On the pre-test, correct answers across questions ranged from 31–88%, while on the post-test, participants responded correctly 88–100% of the time. Related-samples Wilcoxon signed-rank test showed a statistically significant difference (P = 0.007) in the post-test scores on the knowledge domain. Qualitative results showed burnout as an unrecognized and unreported issue, and its drivers included stigma and feelings of helplessness. Participants praised the interventions and reported that they translated learned skills into practice. Conclusion In this proof-of-concept study, we found that educational interventions developed using a theory-driven framework to meet the unique needs of rural healthcare workers are acceptable and feasible. Future studies can test the intervention impact in well-powered trials to support scale-up efforts to identify and address burnout.